The Investigation about the Heritage over Generations for the Family Enterprise and Firms Financialization Process. (3rd October 2022) - Liu, Hui
Abstract : From the reform and opening up to the present, family businesses have become an important pillar of my country's national economy and the most essential push power to the advancement of the Economy of China. At present, more and more family firms come to the top of the hill on the heritage over generations. Meanwhile, the right of owning the firm has changed from the inventor or creators to the descendant ones and it is a must for them to inherit to the advancement. The intergenerational inheritance of family businesses has also had a certain impact on the global economy. At present, China's real economy is in a critical period of transformation and upgrading and industrial upgrading. At the same time, the weakening of the real economy. On the contrary, with the increasing popularity and deepening development of the financial industry, a large number of non-financial companies have turned their investment goals to the financial industry to obtain high returns. Of course, the company's financialization must have its positive side, and naturally, there is also a negative side. There are opportunities for enterprises to obtain high profits, but there are also great investment and management risks. Therefore, before financial investment, we should also fully consider the business risks borne by family enterprises. In addition, because of the particularity of the ownership of family enterprises in China, there are great differences in many aspects compared with other family enterprises and non-family enterprises abroad and internationally. Therefore, there may be some differences in the impact of corporate financialization on them. This study will further study and analyze the internal factors and modes of family business intergenerational inheritance leading to enterprise financialization based on family emotional wealth theory and representative theory, combined with the process of family business intergenerational inheritance and family business financialization. In the theoretical part, it combs the literature, including the definition of intergenerational inheritance, influencing factors, and inheritance content. Through the empirical test of the intermediary effect, this paper analyzes and studies the direct impact and intermediary effect of the proportion of productive investment on the intermediary effect; the role of family business identity (most important for children), re measure explanatory variables, and use PSM, propensity score matching method to test the robustness of regression results.